Microplastics in large marine herbivores: Florida manatees (Trichechus manatus latirostris) in Tampa Bay - Gowans, Shannon; Siuda, Amy N. S. (Frontiers in Ecology and Evolution, 2023)
Although there is growing concern about ingestion of microplastics by marine organisms, little research has been conducted on marine herbivores. This is the first study to document microplastic ingestion within the family Sirenia. Subsamples were collected from five locations in the gastrointestinal tracts (GI) of 26 dead manatees (Trichechus manatus latirostris) from Tampa Bay, Florida. During gross necropsies, macroplastic pieces were found in seven individuals (26.9%). Careful visual examination of the subsampled portions of the GI contents indicated that 19 individuals (73.1%) contained plastic particles. As five individuals had both macro and microplastic pieces, the overall frequency of occurrence of plastic ingestion was 76.9%. Due to the large volume of cellulose-rich ingested material, it was not feasible to analyze the entire gut contents, nor was it feasible to conduct chemical or enzymatic digestion; therefore, it is very likely that many microplastic pieces were not detected. Despite these technical challenges, it is clear that manatees in Tampa Bay are routinely consuming microplastics in addition to larger plastic pieces. Currently, nothing is known about the physiological effects of microplastic ingestion in sirenians, however environmental plastics could be concentrated by manatees through ingestion and the subsequent production of microplastics-laden feces.